Natural Rubber Films Incorporated with Red Propolis and Silver Nanoparticles Aimed for Occlusive Dressing Application - Garcia,Charlene Silvestrin Celi (2021)
Abstract In this work, NRL films were enriched with red propolis and silver nanoparticles with the aim of obtaining dressings with bactericide properties. To improve the properties of these materials, plasma treatment was also applied to the films. Cytotoxic effects were evaluated by MTT and agar diffusion assays on secondary and stem cells. Determination of cell behavior on the films were assessed by EDS and FEG-SEM. In general, the plasma modified NRL films presented hydrophilic character, favorable condition for biomedical applications. RBS results showed that silver is probably in nanoparticulate form. MTT assays revealed that non-cytotoxic effects were observed for all the samples extracts. Either the plasma treatment or silver deposition were effective in sterilizing the samples and modifying their surfaces. It was demonstrated in this in vitro study that ADSCs associated with NRL films enriched with propolis should be considered promising for application in the healing of occlusive wounds.